Amyotrophic Lateral Sclerosis (ALS): Stressed by Dysfunctional Mitochondria-Endoplasmic Reticulum Contacts (MERCs) - Junsheng Chen; Arthur Bassot; Fabrizio Giuliani; Thomas Simmen (Cells, 2021)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease for which there is currently no cure. Progress in the characterization of other neurodegenerative mechanisms has shifted the spotlight onto an intracellular structure called mitochondria-endoplasmic reticulum (ER) contacts (MERCs) whose ER portion can be biochemically isolated as mitochondria-associated membranes (MAMs). Within the central nervous system (CNS), these structures control the metabolic output of mitochondria and keep sources of oxidative stress in check via autophagy. The most relevant MERC controllers in the ALS pathogenesis are vesicle-associated membrane protein-associated protein B (VAPB), a mitochondria-ER tether, and the ubiquitin-specific chaperone valosin containing protein (VCP). These two systems cooperate to maintain mitochondrial energy output and prevent oxidative stress. In ALS, mutant VAPB and VCP take a central position in the pathology through MERC dysfunction that ultimately alters or compromises mitochondrial bioenergetics. Intriguingly, both proteins are targets themselves of other ALS mutant proteins, including C9orf72, FUS, or TDP-43. Thus, a new picture emerges, where different triggers cause MERC dysfunction in ALS, subsequently leading to well-known pathological changes including endoplasmic reticulum (ER) stress, inflammation, and motor neuron death.